Longitudinal study of mammary microbiota dynamics and mastitis prevention in Holstein cows by dry-off strategy - Wang, Xinyu; Liu, Jing; Jiang, Lin; Sun, Tingting; He, Xiaolei; Yang, Lijiao; Liu, Mingchun; Xu, Fei (Frontiers in Veterinary Science, 2026)
IntroductionConducting a dry-off period during the late lactation phase in dairy cows can reduce the incidence of clinical mastitis both during the dry period and after subsequent calving. The primary dry-off methods include the application of antibiotics alone or in combination with internal teat sealants. A thorough understanding of the mammary gland microbiota composition before and after dry-off is essential for developing scientifically sound dry-off protocols in practical dairy production.MethodsFive Holstein cows approaching dry-off were selected for this study. The day of calving is designated as Day 0. Milk samples were collected at three time points around the drying period for 16S rRNA gene sequencing to investigate the differences in mammary microbial composition during these stages. Including Group A (−95 to −67 days), Group B (1 to 2 days), and Group C (14 days).ResultsThe results showed that compared to Group A, the abundance of Firmicutes, Actinobacteria, and Bacteroides, as well as the genera Psychrobacter, Romboutsia, Clostridium sensu stricto 1, Turicibacter, Corynebacterium, Staphylococcus, Streptococcus, and Pseudonocardia (all Gram-positive bacteria) in the milk samples of Group B was significantly lower. In addition, the microbial diversity and richness in the milk samples of Groups A and C exhibited highly significant differences compared to those of Group B (p ≤ 0.001). However, no significant differences were found in the microbial communities of the milk samples between Groups A and C (p > 0.05). Furthermore, the abundance of beneficial bacterial genera such as Lactobacillus was also increased by antibiotic treatment.ConclusionThis exploratory study preliminarily indicates that a single dose of cefapirin benzathine administered via intramammary infusion before drying-off can effectively reduce the abundance of specific mammary pathogens, including Staphylococcus, Streptococcus, and Corynebacterium (all Gram-positive bacteria). Furthermore, the diversity and richness of the mammary microbiota generally recovered approximately 14 days after calving. These findings provide a temporal framework for the reconstruction of the mammary microbiota in dairy cows following the dry period.